Fluorescence sensing platform for Cronobacter sakazakii based on the cationic metal-organic frameworks modified upconversion nanoparticles. (March 2023) - Yin, Mingyuan; Wang, Zedan; Xie, Peijuan; Han, Lirong; Li, Linsen; Wang, Haiyan; Qiao, Xiaoqiang; Deng, Qiliang
Abstract: Cronobacter sakazakii ( C. sakazakii ) is a serious threat to human health. Efficient detection of C. sakazakii is crucial for food safety and the control of foodborne diseases. Here, a fluorescence sensing platform for C. sakazakii was constructed with α-glucosidase and cationic metal-organic framework-functionalized upconversion nanoparticles (UCNPs@MOFs). The anionic α-glucosidase was inhibited by binding to cationic UCNPs@MOFs. The presence of C. sakazakii competitively combined with cationic UCNPs@MOFs and released α-glucosidase into the enzyme substrate solution ( para -nitrophenyl-α-d -glucopyranoside) to recover activity, thus triggering fluorescence quenching of cationic UCNPs@MOFs through the product of 4-nitrophenol. In addition, α-glucosidase from C. sakazakii accelerated the formation of 4-nitrophenol, thus improving the fluorescence response of cationic UCNPs@MOFs. This strategy illustrates high sensitivity of the designed platform for C. sakazakii with a wide linear range (1.1 × 10 2 –1.1 × 10 8  cfu mL −1 ), a low limit of detection (3.2 × 10 1  cfu mL −1 ), and an acceptable recovery value (85.2–111.5%) in real samples (tap water, infant formula powder, and goat milk powder). These results confirm that the proposed fluorescence platform is an ideal candidate tool for the detection of C. sakazakii in microbiological diagnostics. Highlights: A highly sensitive and rapid fluorescence sensor for Cronobacter sakazakii was developed. The advantage of sensor based on the excellent fluorescence of functionalized upconversion nanoparticles probes. The quenching was mainly arising from the competitive combination of UCNPs probes and the anionic enzyme. A broad linear range (1.1 × 10 2 -1.1 × 10 8  cfu mL −1 ) and a high sensitivity (3.2 × 10 1  cfu mL −1 ). Cronobacter sakazakii in real samples (tap water, infant formula powder and goat milk powder) were successfully detected.